Early onset but long survival and other prognostic factors in Chinese sporadic amyotrophic lateral sclerosis. (November 2019) - Liu, Tanxin; Shen, Dongchao; Yang, Xunzhe; Cui, Bo; Tai, Hongfei; Wang, Zhili; Liu, Shuangwu; Zhang, Kang; Liu, Mingsheng; Cui, Liying
Highlights: Early onset but long survival in Chinese amyotrophic lateral sclerosis patients. Survival rate is significantly different between age groups. More bulbar onset and less lumbosacral onset cases in aging group. Abstract: Objectives: To explore the cause of long survival but early onset and other prognostic factors among Chinese sporadic amyotrophic lateral sclerosis (ALS) patients. Methods: Patients with ALS were recruited and followed up from Jan 2013 to Jan 2017. Phenotype and survival were compared among different age-at-onset groups. Candidate prognostic factors were analyzed by Kaplan-Meier method, Cox regression and Royston Parmar (RP) model dealing with breaches of proportional hazard assumption. Results: In the cohort of 531 patients, mean age-at-onset was 53.68 years (SD:10.85) and overall estimated median survival time was 59 months (95% CI: 48.29–69.71). Pairwise comparison showed that patients above 65 years at onset were more frequently bulbar onset (adjusted residual: 3.0), less frequently lumbosacral onset (adjusted residual: −3.0), and had shorter survival compared with other age groups (p = 0.002). Cox and RP model demonstrated independent prognostic variables including age at onset, bulbar onset, diagnostic delay, MRC-score at first diagnosis and region of residence. Conclusions: This clinic-based study suggested that Chinese sporadic ALS patients had relatively long survival probably due to young age and less bulbar onset cases. Short diagnostic delay, low MRC-score and northern residence were also predicative of short survival. Reallocation of resources is needed to optimize quality care and prolong survival time.